Mengoptimalkan Potensi Ekonomi Digital Melalui Komunikasi Digital pada Upacara Mulud Adat Bayan - Ashar Banyu Lazuardi; Mohamad Yudisa Putrajip; Lalu Yayan Ardiansyah (Universitas Bumigora, 2026)
The Bayan Customary Mulud Ceremony is an intangible cultural heritage of the Sasak people. Ithas the potential to be a cultural tourism attraction and a source for digital economy development.However, this potential has not been fully utilized because current digital communication failsto connect cultural values with economic opportunities for the community. This researchaims to analyze the digital economy potential of the Bayan Customary Mulud Ceremony byexamining the government’s digital communication and empirical conditions in the field. Theresearch uses a qualitative approach with a case study method. Data was collected throughnon-participatory observation during the ceremony and analysis of the West Nusa TenggaraProvincial Government’s official tourism promotion website. The results show that digitalcommunication is still focused on destination promotion and has not integrated cultural economic potential. Information about the Bayan Customary Mulud does not highlight the philosophical values of the ritual, the event calendar, or the economic opportunities that can be developed. In the field, tourists are still mostly local visitors, micro, small, and medium enterprises (MSMEs) operate independently, and the spatial arrangement for tourists is not yet optimal. This research concludes that digital economy development requires a digital communication strategy that integrates digital storytelling, cultural promotion, MSME empowerment, and indigenous community-based destination management to create sustainable cultural tourism.